2022
DOI: 10.7554/elife.79077
|View full text |Cite
|
Sign up to set email alerts
|

Munc13 supports fusogenicity of non-docked vesicles at synapses with disrupted active zones

Abstract: Active zones consist of protein scaffolds that are tightly attached to the presynaptic plasma membrane. They dock and prime synaptic vesicles, couple them to voltage-gated Ca2+ channels, and direct neurotransmitter release towards postsynaptic receptor domains. Simultaneous RIM+ELKS ablation disrupts these scaffolds, abolishes vesicle docking and removes active zone-targeted Munc13, but some vesicles remain releasable. To assess whether this enduring vesicular fusogenicity is mediated by non-active zone-anchor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…2c-e) at levels similar to (PDZ-C2A-P) or above (Zn-C2B) those for RIM1α, indicating targeting to the active zone. As described before 26,34,63 , the active zone was disrupted in cQKO R+E neurons with very low levels of Munc13-1, and robust reductions in Ca V 2.1 and RIM-BP2. The postsynaptic marker PSD-95 was unaltered, and Liprin-α3 was increased by ∼30%, in agreement with previous work 34 and with an upstream function 22,23,25 .…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…2c-e) at levels similar to (PDZ-C2A-P) or above (Zn-C2B) those for RIM1α, indicating targeting to the active zone. As described before 26,34,63 , the active zone was disrupted in cQKO R+E neurons with very low levels of Munc13-1, and robust reductions in Ca V 2.1 and RIM-BP2. The postsynaptic marker PSD-95 was unaltered, and Liprin-α3 was increased by ∼30%, in agreement with previous work 34 and with an upstream function 22,23,25 .…”
Section: Resultssupporting
confidence: 60%
“…Removing both proteins at the same time disrupts both complexes and induces strong synapse assembly defects 69 . We propose that the sub-structuring of the active zone that we describe here accounts for the resilience of synapse and active zone assembly that is often observed in loss-of-function studies 12,26,34,63,69,82,86 . (c-q) Example STED images, average line profiles and quantification of the peak intensities of HA and PSD-95 (c-e), Munc13-1 (f-h), CaV2.1 (i-k), Liprin-α3 (l-n) and RIM-BP2 (o-q) at excitatory side-view synapses identified by Synaptophysin (Syp) and PSD-95.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, whether changing properties within single Munc13- 1 NCs affects functions in docking and priming remains an open question of intense interest. Though reducing Munc13 content by knockout alters both processes (47, 50), Karlocai et al (2021) argue that the high docked vesicle occupancy at release sites (5, 33) suggests that varying Munc13-1 content per release site may principally control release probability at these sites, consistent with a potential effect on vesicle priming (33). Our findings are also consistent with previous work that suggests Schaffer collateral synapses onto CA1 interneurons have a high probability of release due, in part, to a larger readily releasable pool (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the readily releasable pool (RRP) often tightly correlates with the pool of docked vesicles (i.e. vesicles in the direct contact with AZ plasma membrane; Imig et al, 2014), but exceptions to this correlation have been also observed (Man et al, 2015; Wang et al, 2016; Tan et al, 2022). Further correlated biophysical-structural approaches are needed to address these questions.…”
Section: Introductionmentioning
confidence: 99%